THE UTILIZATION OF INFORMATION TECHNOLOGY AND COMMUNICATION AS A DISTRIBUTION CHANNEL IN INCREASING THE COMPETITIVENESSOF LOCAL BUSINESS IN TOURISM INDUSTRY (Case study: Homestay inUbud Village, Bali) - Sukma Winarya Prabawa, I Wayan (Pusat Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Nusa Dua Bali, 2018)
The priority of tourism development in Indonesia covers the development of homestay, digitization and air connectivity.The purpose of this study is to explore the utilization of ICT in its relation to distribution channels used by home stay owners in Ubud as a form of small medium business owned by local communities. Data collection techniques used were stratified random sampling, secondary research, focus group discussion and in depth interview. Through qualitative descriptive analysis techniques, the results of this study concluded that most of home stays in Ubud is familiar with ICTand has now become a major distribution channel that contributes greatly to the occupancy of home stay.